PENYULUHAN KESELAMATAN DAN KESEHATAN KERJA (K3) DAN PELATIHAN ALAT PELINDUNG DIRI (APD) DI PABRIK TAHU FROLARIS - Wahdi, Achmad; Retno Puspitosari, Dewi (Jurnal LENTERA, 2025)
Occupational Safety and Health (K3) is a program created for workers or laborers and employers as a form of prevention against work accidents and diseases due to work relationships that may occur to workers in the work environment. Personal protective equipment (PPE) is a tool used by workers to protect the entire body or part of the body against potential hazards or work accidents in the workplace. The purpose of providing K3 counseling and personal protective equipment (PPE) training is to provide knowledge of K3 and the benefits of PPE. This method is carried out by providing counseling on Occupational Safety and Health and PPE training to workers in the Floralis tofu factory. From the results before being given counseling on Occupational Safety and Health and PPE training, 44% were obtained and after being given counseling it became 56%, this community service is to improve the Occupational Health and Safety (K3) of workers in the Floralis tofu factory. In addition, there are several outputs that will be in this service, namely increasing efforts to ensure the orderly use of Personal Protective Equipment, promotive and preventive handling of workers with work-related accident problems. Work accidents and work-related illnesses occur in workers so that workers are entitled to social security, for this reason the Government has created the Jamsostek Program which is regulated in the Law on Social Security for Workers as recognition of the rights of workers to obtain social security.